2011
DOI: 10.1364/ol.36.002432
|View full text |Cite
|
Sign up to set email alerts
|

Bandgap guidance in hybrid chalcogenide–silica photonic crystal fibers

Abstract: We report a hybrid chalcogenide-silica photonic crystal fiber made by pressure-assisted melt-filling of molten glass. Photonic bandgap guidance is obtained at a silica core placed centrally in a hexagonal array of continuous centimeters-long chalcogenide strands with diameters of 1.45 μm. In the passbands of the cladding, when the transmission through the silica core is very weak, the chalcogenide strands light up with distinct modal patterns corresponding to Mie resonances. In the spectral regions between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 18 publications
3
47
0
1
Order By: Relevance
“…2b). Finally we note that the micro-Raman spectrum of the chalcogenide glass is identical before and after pumping into the silica capillary, suggesting that the bulk properties of the glass are not affected by melt-filling [14].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…2b). Finally we note that the micro-Raman spectrum of the chalcogenide glass is identical before and after pumping into the silica capillary, suggesting that the bulk properties of the glass are not affected by melt-filling [14].…”
Section: Introductionmentioning
confidence: 73%
“…Here we report SC generation from 60 fs pulses at 1550 nm in a dispersion-tuned chalcogenide-silica step-index fiber fabricated by pressure-assisted melt-filling [14][15][16] (Fig. 1a).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Upon infiltration of the PCF air capillaries with a high refractive index medium, the coupling of light between the core and the microstructured cladding of the fibre is altered, leading to measurable distinctive features in the optical spectra. In recent years, the infiltration of PCF capillaries with high refractive index materials such as polymers [16], ferrofluids [17], and glasses [18,19], has been highlighted for the realization of novel in-fibre devices suitable for sensing applications, magnetometers, and supercontinuum generation. On a similar manner nanoparticles attached on the internal capillary walls have been used to induce plasmonic cladding structures, and plasmonic tuned fibres for sensing applications are realized following such route [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups around the globe are working towards the development of novel tunable fiber devices by combining different advanced optical materials with PCFs, such as polymeric organosilicon compounds [12][13][14] , liquid crystals 15 , chalcogenide glasses 16,17 , etc. Recently it has been shown that even softglasses can be integrated within polymer PCFs 18 .…”
mentioning
confidence: 99%